Seasonal prediction and possible causes of sudden losses of sea-ice in the Weddell Sea in recent years based on potential oceanic and atmospheric factors - Zhao, Hui-Jun; Xiao, Dong; Bian, Lin-Gen; Wu, Wei; Yang, Hai-Wei; Chen, Qi; Liang, Tian; Sun, Lan-Dong (Frontiers in Environmental Science, 2023)
Seasonal prediction of the sea-ice concentration (SIC), especially the sudden loss events, is always a challenging issue. The Weddell Sea SIC experienced two unprecedented decline events, falling from 2.21% in austral winter of 2015 to 0.02% in austral summer of 2016 and then falling to -2.32% in austral spring of 2017. This study proposed several statistical prediction models for Weddell Sea SIC and performed in the period including the sudden decline events. We identified the six potential oceanic and atmospheric factors at different leading times related to the variability of Weddell Sea SIC, including the Pacific Decadal Oscillation (PDO), Atlantic Multidecadal Oscillation (AMO), Niño12 sea surface temperature (SST), Southeastern Indian Ocean (SEIO) SST, Antarctic sea level pressure (SLP) and Weddell Sea surface air temperature (SAT). Multiple linear regression models were employed to establish equations to simulate the variation of Weddell Sea SIC under three groups of climate factors during 1979–2012. These models could well reproduce the low-frequency variation of SIC in the Weddell Sea during the simulating period, and the high-frequency values through two kinds of error correction methods developed in this study. After correcting by the error correction methods developed in this study, the correlation coefficients (absolute errors) of these models were enhanced (decreased) during the simulated period. In the predicting period of 2013–2018, the corrected models generally well predicted the sudden losses of Weddell Sea SIC. The possible primary influencing factors of these sudden losses of Weddell Sea SIC were the PDO, Niño12 SST, Southern Annular Mode (SAM) and SAT during 2015–2016 and the AMO, PDO, Niño12 SST, SAM, and SAT during 2016–2017.